Pengaruh Sistem Informasi Akuntansi Manajemen, Gaya Kepemimpinan, Trust, dan Ketidakpastian Lingkungan terhadap Kinerja Manajerial - Lalu Takdir Jumaidi; Baiq Anggun Hilendri Lestari; Rahman Rahman (Sekolah Tinggi Ilmu Ekonomi AMM, 2021)
This study aims to examine the effect of the information systems of management accounting, leadership style, trust, and environmental uncertainty on managerial performance. The test was carried out on forty managers of sharia cooperatives in Lombok. The type of research is associative. The type of data used in this research is quantitative using primary data. Data processing techniques in this study were calculated by SEM-based variants (SEM PLS) using a smart PLS software application. The results of this study showed that environmental uncertainty has a significant effect on managerial performance, while the information system of management accounting, leadership style, and trust have an effect but not significant on managerial performance. The results of the finding of this study have an implication for sharia cooperatives, both sharia cooperative managers, supervisors, and members of sharia cooperatives in general, especially in Lombok in making decisions to formulate policies related to the implementation of management accounting information systems, leadership style, trust and being able to anticipate environmental uncertainty and can create right decisions to improve managerial performance.